Evaluation of Liver Function Through SGOT and SGPT Quantification in Rats Administered Polyethylene Terephthalate Microplastics - Diana Nadhifah; Hartalina Mufidah; Ahdiah Imroatul Muflihah (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2025)
Background: Microplastics, as emerging environmental pollutants, can accumulate in target organs such as the liver and induce hepatotoxicity through oxidative stress mechanisms. Purpose: To determine the effect of PET microplastic exposure at various doses on liver transaminase enzyme levels (SGOT and SGPT) in white rats. Methods: This experimental study used 25 male white rats (Rattus norvegicus), aged 8–10 weeks, divided into five groups (n=5 per group): control (distilled water), P1 (0.4 mg/day), P2 (0.6 mg/day), P3 (0.8 mg/day), and P4 (1.0 mg/day) of orally administered PET microplastics for 28 days. SGOT and SGPT levels were measured using spectrophotometry. Statistical analysis was performed using ANOVA followed by Tukey-HSD or Bonferroni post hoc tests (α=0.05). Results: The SGPT level in the control group (61.48 ± 7.50 U/L) significantly increased to 114.40 ± 7.71 U/L (P1), 132.22 ± 18.41 U/L (P2), 191.78 ± 16.42 U/L (P3), and 227.26 ± 12.23 U/L (P4). The SGOT level in the control group (78.64 ± 9.48 U/L) significantly increased to 188.46 ± 2.55 U/L (P1), 195.10 ± 5.75 U/L (P2), 238.90 ± 41.34 U/L (P3), and 310.74 ± 26.66 U/L (P4). Statistical analysis revealed significant differences among groups (p < 0.05). The higher the PET microplastic dose, the higher the SGOT and SGPT levels observed. Conclusions: ET microplastic exposure induces hepatotoxicity, as evidenced by dose-dependent increases in SGOT and SGPT levels.